Secondary bacterial infections of buruli ulcer lesions before and after chemotherapy with streptomycin and rifampicin. - Dorothy Yeboah-Manu; Grace S Kpeli; Marie-Thérèse Ruf; Kobina Asan-Ampah; Kwabena Quenin-Fosu; Evelyn Owusu-Mireku; Albert Paintsil; Isaac Lamptey; Benjamin Anku; Cynthia Kwakye-Maclean; Mercy Newman; Gerd Pluschke (Public Library of Science (PLoS), 2013)
Buruli ulcer (BU), caused by Mycobacterium ulcerans is a chronic necrotizing skin disease. It usually starts with a subcutaneous nodule or plaque containing large clusters of extracellular acid-fast bacilli. Surrounding tissue is destroyed by the cytotoxic macrolide toxin mycolactone produced by microcolonies of M. ulcerans. Skin covering the destroyed subcutaneous fat and soft tissue may eventually break down leading to the formation of large ulcers that progress, if untreated, over months and years. Here we have analyzed the bacterial flora of BU lesions of three different groups of patients before, during and after daily treatment with streptomycin and rifampicin for eight weeks (SR8) and determined drug resistance of the bacteria isolated from the lesions. Before SR8 treatment, more than 60% of the examined BU lesions were infected with other bacteria, with Staphylococcus aureus and Pseudomonas aeruginosa being the most prominent ones. During treatment, 65% of all lesions were still infected, mainly with P. aeruginosa. After completion of SR8 treatment, still more than 75% of lesions clinically suspected to be infected were microbiologically confirmed as infected, mainly with P. aeruginosa or Proteus miriabilis. Drug susceptibility tests revealed especially for S. aureus a high frequency of resistance to the first line drugs used in Ghana. Our results show that secondary infection of BU lesions is common. This could lead to delayed healing and should therefore be further investigated.